Complete Luteolysis and Pregnancy Per Insemination After Modifying the Standard 7-day Ovsynch Program in Dairy Cows - J. S. Stevenson; B. Atanasov (Kansas Agricultural Experiment Station Research Reports, 2020)
Two experiments were conducted with Holstein-Friesian cows in the Republic of North Macedonia and with Holstein cows in Kansas. We hypothesized that a single standard dose of PGF2αinjected on day 8 instead of day 7 in the standard Ovsynch program would increase the proportion of cows with complete luteolysis and increase the synchronization risk compared with control cows receiving a standard dose on day 7. Cows were treated with the standard program (Ov-7x1) or with Ov-8x1 experimental program in experiment 1, using only a single dose of PGF2α. In experiment 2, a third treatment was added (Ov-7x2), in which a second dose of PGF2αwas administered 24 hours after the first dose. Overall, the results in experiment 1 demonstrated a greater percentage of multiparous cows in the OV-8x1 treatment had complete luteal regression compared with multiparous Ov-7x1 cows, whereas treatments were equally effective in primiparous cows. In contrast, results in experiment 2 revealed nearly 100% of cows in the Ov-7x2 treatment receiving the second dose of PGF2αhad complete luteolysis. In both experiments, when the status of luteal function before PGF treatment was examined, the treatments were equally effective in causing complete luteal regression. Pregnancy rates, however, did not differ among treatments indicating that any of the three treatments will likely produce similar pregnancy outcomes with the flexibility of applying either the 7- vs. 8-day treatments.
Keywords: Ovsynch duration; prostaglandin F2α; dairy cow; luteolysis; pregnancy rate